Main Directions Of Integrated And Innovative Development Of Territories - SAYFULLAYEVNA, KHUSANOVA GULCHEKHRA; EGAMBERDIYEVICH, HUDAYBERDIYEV ULMASJON; KHOLDAROVNA, UMAROVA NARGIZA; BARNAYEVNA, ODILOVA DILNOZAKHON (The journal of contemporary issues in business and government, 2021)
This article describes the main directions of integrated innovative regional development, it consists in ensuring sustainable economic development of the region, improving the quality of life of the population and the environment of a certain territory.